Some aspects of the Lithuanian banking sector transformation - Aleknavičiene, Aušra; Tvaronavičiene, Manuela (Journal of Business Economics and Management, 2006)
The paper deals with changes in Lithuanian banking sector, which occurred during the 1996–2005 period. Authors highlight main driving force – foreign direct investments (FDI) into sector. Structure‐conduct‐performance (SCP) approach for sector transformation analysis has been adapted and applied. Change of a set of indicators incorporated into presented variation SCP is being commented. On that basis authors evaluate transformations of banking sector in terms of number and capital origin of market players, sector expansion, concentration and financial performance efficiency. Assumption about more efficient functioning of foreign banks in less developed countries is being discussed; considerations concerning foreign capital impact, taking into account positive and negative plausible facets presented.Firstd Published Online: 14 Oct 2010